PENINGKARAN KARAKTER DENGAN ORGANISASI LUAR SEKOLAH - Itsna Rusydiana; Nur Fadhilah, Isnaini; Fediana Mustofa, Dise; Hakim, Lukman; Nur Hidayati, Maidina; Rahmawati, Aullia (LPPM STAI Muhammadiyah Probolinggo, 2022)
Abstract The Ngreco branch of the IPNU-IPPNU organization plays a crucial role in shaping individual character through a series of activities held by its management, including khataman, carnival and management meetings. Active support from the surrounding community, both in the form of direct participation and provision of facilities, is an important factor in the success of organizational activities. Continuous interaction between organizational members and the community is a strategy to maintain this support. When facing obstacles, the management and members of the organization carry out deliberations and evaluations to improve the implementation of activities in the future. Organization members, as resource persons, demonstrated the positive impact of their participation in organizational activities, including increasing self-confidence and building good character. Despite admitting a lack of experience in carrying out leadership roles, members still try to overcome obstacles, showing the development of the character of independence and cohesion within the organization. Collaboration with other organizations is also part of the strategy to strengthen friendship and collaboration in organizational activities. Overall, the roles and interactions within the Ngreco branch of the IPNU-IPPNU organization strengthen the formation of quality youth character. Keywords: Ngreco branch of the IPNU-IPPNU organization; Formation of adolescent character.